Chronic morphine administration enhances nociceptive sensitivity and local cytokine production after incision - Angst Martin S; Qiao Yanli; Shi Xiaoyou; Liang DeYong; Yeomans David C; Clark J (SAGE Publishing, 2008)
Abstract Background - The chronic use of opioids prior to surgery leads to lowered pain thresholds and exaggerated pain levels after these procedures. Several mechanisms have been proposed to explain this heightened sensitivity commonly termed opioid-induced hyperalgesia (OIH). Most of these proposed mechanisms involve plastic events in the central or peripheral nervous systems. Alterations in the abundance of peripheral mediators of nociception have not previously been explored. Results - In these experiments mice were treated with saline (control) or ascending daily doses of morphine to generate a state of OIH followed by hind paw incision. In other experiments morphine treatment was initiated at the time of incision. Both mechanical allodynia and peri-incisional skin cytokine levels were measured. Myeloperoxidase (MPO) assays were used to determine neutrophil activity near the wounds. The cytokine production inhibitor pentoxifylline was used to determine the functional significance of the excess cytokines in previously morphine treated animals. Mice treated chronically treated with morphine prior to incision were found to have enhanced skin levels of IL-1β, IL-6, G-CSF, KC and TNFα after incision at one or more time points compared to saline pretreated controls. The time courses of individual cytokines followed different patterns. There was no discernable effect of chronic morphine treatment on wound area neutrophil infiltration. Pentoxifylline reduced cytokine levels and reversed the excess mechanical sensitization caused by chronic morphine administration prior to incision. Morphine treatment initiated at the time of incision did not lead to a generalized enhancement of cytokine production or nociceptive sensitization in excess of the levels observed after incision alone. Conclusion - The enhanced level of nociceptive sensitization seen after incision in animals chronically exposed to morphine is associated with elevated levels of several cytokines previously reported to be relevant to this incisional pain model. The cytokines may be functional in supporting nociceptive sensitization because pentoxifylline reverses both peri-incisional skin cytokine levels and OIH. Opioid administration beginning at the time of incision does not seem to have the same cytokine enhancing effect. Approaches to postoperative pain control involving a reduction of cytokines may be an effective way to control excessive pain in patients chronically using opioids prior to surgical procedures.